2013
DOI: 10.1039/c3em00078h
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of field portable X-ray fluorescence spectrometry for the in situ determination of heavy metals in soils and plants

Abstract: In soil pollution studies, large numbers of soil samples collected at random need to be processed and analyzed to determine their heavy metal contents. This study was designed to assess the use of a field portable X-ray fluorescence (FPXRF) spectrometry system for the in situ determination of heavy metal levels in both soil and plant samples. First, we optimised the method using 84 reference soil standards and soil samples from known polluted sites. The optimised method was then used to determine heavy metals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 12 publications
3
20
2
Order By: Relevance
“…If mobile XRF spectrometry could evaluate the concentrations of chemical substances in environmental water, the investigation of water quality could be conducted simultaneously with a survey of the surrounding environment such as soil [15,16], minerals [17,18], and waste [19] in the field. This would be helpful in the rapid specification and removal of pollutant sources.…”
Section: Introductionmentioning
confidence: 99%
“…If mobile XRF spectrometry could evaluate the concentrations of chemical substances in environmental water, the investigation of water quality could be conducted simultaneously with a survey of the surrounding environment such as soil [15,16], minerals [17,18], and waste [19] in the field. This would be helpful in the rapid specification and removal of pollutant sources.…”
Section: Introductionmentioning
confidence: 99%
“…Yet another factor which could have influenced the Pb results is the occurrence of interferences. Gutiérrez-Ginés et al ( 2013 ) also reported inaccuracy for Pb at lower concentrations. In their discussion, they mention the possibility of interference from As.…”
Section: Resultsmentioning
confidence: 92%
“…According to prior knowledge of the concentrations and distributions of pollutants at this site (Gutiérrez‐Ginés et al, 2013), we collected soil from the most polluted zone for our experiment. The topsoil layer (0–20 cm) was carefully collected using a hoe to avoid disrupting its structure after cutting all vegetation back to the soil surface.…”
Section: Methodsmentioning
confidence: 99%
“…W hen trying to ameliorate the impacts of old abandoned mines on land ecosystems, the main problems faced are related to high concentrations of phytotoxic metals in top soil layers (Gutiérrez‐Ginés et al, 2013), along with low soil nutrient contents. Some researchers have highlighted that soils containing heavy metals are among the most difficult to restore.…”
mentioning
confidence: 99%